Huidouba Improved Podocyte Injury by Down-Regulating Nox4 Expression in Rats With Diabetic Nephropathy - Yang, KunBao; Bai, YingHui; Yu, Ning; Lu, BiNan; Han, GuiYan; Yin, ChangJiang; Pang, ZongRan (Frontiers in Pharmacology, 2020)
Diabetic nephropathy (DN), as the most common microvascular complication of diabetes mellitus (DM), has become one of the leading causes of end-stage renal disease (ESRD). Numerous studies have indicated that podocyte loss plays an important role in the development of DN and can even cause proteinuria in the early stage of DN. In the study, we found that Huidouba (HDB) significantly decreased the level of fasting blood glucose (FBG), the ratio of microalbumin to urine creatine (mAlb/Ucr), serum creatine (Scr), serum urea nitrogen (BUN), and malondialdehyde (MDA) in the kidney and downregulated the expression of Nox4 predominantly in glomerular tissue while upregulating nephrin expression in DN rats. In addition, HDB could also reduce podocyte damage and glomerular basement membrane (GBM) pathologic changes, as shown by transmission electron microscopy (TEM). In vitro study showed that HDB could inhibit high glucose (HG)-induced Reactive Oxygen Species (ROS) production and protect against podocyte apoptosis by downregulated Nox4 expression in podocytes. These results may provide a scientific basis for developing HDB as a potential folk medicine for the treatment of DN.